1330 Assessing the impact of investigation checklists in paediatric intensive care unit. (17th August 2022) - Jackson, Simon; Alcorn, Claire; McKenna, Dearbhla; Stevenson, Kim; Mallet, Peter; Richardson, Julie
Abstract : Aims: Checklists are a valued cognitive aid, used in multiple specialities, and are effective tools for decreasing morbidity, mortality and improving efficiency in emergency and non-emergency situations. 1, 2 Within a United Kingdom Paediatric Intensive Care Unit (PICU), collaborations between different specialities identified areas to create investigations checklists (IC) for a variety of clinical presentations to improve efficiency and create a standardised approach. We surveyed PICU nurses, junior doctors, ANPs and consultants to assess perceptions of benefits, limitations and areas of improvements for the IC. Methods: The ICs were developed from national and international guidelines and articles, and approved jointly by the speciality team and PICU consultants in August 2021. The IC developed were for Reduced Consciousness, Systemic Onset Juvenile Idiopathic Arthritis, Empyema, Stroke, Vasculitis, Haemophagocytic Lymphohistiocytosis and Macrophage Activating Syndrome, and Microbiology and Virology. The IC consists of a A4 page, with the investigations, laboratory sampling bottles and volumes presented alongside. Nursing and medical staff were trained on IC use before implementation into clinical practice. Three months later, a face to face interviews of PICU nursing and medical staff, was conducted via a questionnaire. Results: A total of 25 staff (7 Junior Doctors/ANP, 3 Consultants, 15 Nurses) were interviewed. Results can be viewed in table 1 . All staff felt positively regarding the benefits for patient care and in the IC's development process. Staff found IC prevented omissions of investigations, provided consistency and enable a quicker diagnosis. Concerns were expressed regarding IC being too prescriptive and a lack of compliance. The majority of staff did not think it reduced nurses work load. To facilitate change in practice continuing frequent reminders of use and junior doctors to write laboratory forms were suggested. Conclusion: This study demonstrates that nursing and medical staff are supportive of IC as a method to enhance patient care. However, nurses are apprehensive this may increase their work load and responsibility. Further work is planned to promote this as tool that all MDT members can contribute too and embed, in a bid to enhance patient care in a critical care setting. References: Haynes AB, Weiser TG, Berry WR, Lipsitz SR, et al. A surgical safety checklist to reduce morbidity and mortality in a global population. N Engl J Med . 2009;360:491-9. Davidson LA, Utarnachitt RB, Mason A, Sawyer T. Development and testing of a neonatal intubation checklist for an air medical transport team. Air Med J . 2018;37:41-45.